Energy Performance of Annual Operation of Heat Pump Coupled with Ground Ice Storage and Photovoltaic/Thermal modules. Issue 1 (1st December 2022) - Noro, Marco; Mancin, Simone; Zilio, Claudio
Abstract: The use of heat pumps for annual climatization is a suitable mean of achieving the 2030 European decarbonization target (-55% with respect to 1990 CO2 emissions). The use of seasonal energy storages allows to store one of the two contemporaneous effects (thermal and cooling energy) produced by the heat pump to be used successively when it is necessary. This paper focuses on a dynamic simulation to size the heating and cooling plant and define a suitable control logic for a refurbished building located in northern Italy. The plant is set up by an electric heat pump in annual operation, coupled with a ground ice storage. Ice produced during heating operation is used in summer to face cooling loads (free cooling). PhotoVoltaic/Thermal modules allow to increase the grid independency and to reduce primary energy consumption of the plant as they can be suitably cooled in any season, by recovering heat for domestic hot water or the ground. A dynamic simulation of the system allows for a full description of the behaviour of the ice tank during the charging and discharging processes. In addition, a primary energy performance analysis of the whole plant is reported, also in comparison to a dual source heat pump configuration for the same building.